Biological materials science : biological materials, bioinspired materials, and biomaterials - Meyers, Marc A., 1946-; Chen, Po-Yu (Cambridge University Press, 2014)
"Taking a unique materials science approach, this text introduces students to the basic concepts and applications of materials and biomedical engineering and prepares them for the challenges of the new interdisciplinary field of biomaterials science. Split into three sections - Basic Biology Principles, Biological Materials, and Bioinspired Materials and Biomimetics - it presents biological materials along with the structural and functional classification of biopolymers, bioelastomers, foams, and ceramic composites. More traditional biomimetic designs such as Velcro are then discussed in conjunction with new developments that mimic the structure of biological materials at the molecular level, mixing nanoscale with biomolecular designs. Bioinspired design of materials and structures is also covered. Focused presentations of biomaterials are presented throughout the text in succinct boxes, emphasising biomedical applications, whilst the basic principles of biology are explained, so no prior knowledge is required. The topics are supported by approximately 500 illustrations, solved problems, and end-of-chapter exercises"--Resumé vydavatele